Proposta de abordagem muticritério para prospecção de leads em agências de marketing digital - Sousa, Rômulo Oliveira de (Universidade Federal Rural do Semi-Árido, 2021)
The search for resource optimization and process improvement is part of the daily routine of every company that seeks sustainable growth. The “time” resource is increasingly precious and there are not always enough inputs to test all available alternatives, with potential for results, in a short period of time. Therefore, it is necessary to give priority to the alternatives with the greatest tendency to generate a positive result. Companies operating in retail and in the goods and services industries live by the same principle: carrying out commercial and financial transactions. Having a sector responsible for managing these transactions is a basic principle of survival in the market. In addition to having a structured commercial sector, the company needs tools and support in decision-making on a daily basis. In the commercial sector of the study company, there is a need to prioritize potential customers (leads) during the commercial team's routine. And it is known that not knowing which leads should be prioritized is a big problem due to potential lost business due to lack of relationship with the team at the right time. Thus, this work aims to apply the SMARTS method to support decision making in prioritizing, in a digital marketing agency in northeastern Brazil. To conduct this study, the SMARTS method was applied to support prospecting in the commercial sector, in prioritizing the service to leads. The method was applied and the alternatives L6, L1, L2, L3 assumed the first 4 ranking positions, with no variation in ranking positions in the sensitivity analysis. Thus, a map of the prioritization model based on the SMARTS method was developed, which is easy and agile to apply in digital marketing agencies and similar companies.
Keywords: Análise multicritério; SMARTS; Priorização de leads; Multicriteria analysis; Lead Prioritization; ENGENHARIAS::ENGENHARIA DE PRODUCAO